Regulation of eIF2α Phosphorylation by Different Functions That Act during Discrete Phases in the Herpes Simplex Virus Type 1 Life Cycle - Mulvey, Matthew (American Society for Microbiology, 2003)
Multiple herpes simplex virus type 1 functions control translation by regulating phosphorylation of the initiation factor eIF2 on its alpha subunit. Both of the two known regulators, the γ(1)34.5 and Us11 gene products, are produced late in the viral life cycle, although the γ(1)34.5 gene is expressed prior to the γ(2) Us11 gene, as γ(2) genes require viral DNA replication for their expression while γ(1) genes do not. The γ(1)34.5 protein, through a GADD34-related domain, binds a cellular phosphatase (PP1α), maintaining pools of active, unphosphorylated eIF2. Infection of a variety of cultured cells with a γ(1)34.5 mutant virus results in the accumulation of phosphorylated eIF2α and the inhibition of translation prior to the completion of the viral lytic program. Ectopic, immediate-early Us11 expression prevents eIF2α phosphorylation and the inhibition of translation observed in cells infected with a γ(1)34.5 mutant by inhibiting activation of the cellular kinase PKR and the subsequent phosphorylation of eIF2α; however, a requirement for the Us11 protein, produced in its natural context as a γ(2) polypeptide, remains to be demonstrated. To determine if Us11 regulates late translation, we generated two Us11 null viruses. In cells infected with a Us11 mutant, elevated levels of activated PKR and phosphorylated eIF2α were detected, viral translation rates were reduced 6- to 7-fold, and viral replication was reduced 13-fold compared to replication in cells infected with either wild-type virus or a virus in which the Us11 mutation was repaired. This establishes that the Us11 protein is critical for proper late translation rates. Moreover, it demonstrates that the shutoff of protein synthesis observed in cells infected with a γ(1)34.5 mutant virus, previously ascribed solely to the γ(1)34.5 mutation, actually results from the combined loss of γ(1)34.5 and Us11 functions, as the γ(2) Us11 mRNA is not translated in cells infected with a γ(1)34.5 mutant.